Structural variation and DNA methylation shape the centromere-proximal meiotic crossover landscape in Arabidopsis - Joiselle B. Fernandes; Matthew Naish; Qichao Lian; Robin Burns; Andrew J. Tock; Fernando A. Rabanal; Piotr Wlodzimierz; Anette Habring; Robert E. Nicholas; Detlef Weigel; Raphael Mercier; Ian R. Henderson (Genome Biology, 2024)
Abstract Background Centromeres load kinetochore complexes onto chromosomes, which mediate spindle attachment and allow segregation during cell division. Although centromeres perform a conserved cellular function, their underlying DNA sequences are highly divergent within and between species. Despite variability in DNA sequence, centromeres are also universally suppressed for meiotic crossover recombination, across eukaryotes. However, the genetic and epigenetic factors responsible for suppression of centromeric crossovers remain to be completely defined. Results To explore the centromere-proximal meiotic recombination landscape, we map 14,397 crossovers against fully assembled Arabidopsis thaliana (A. thaliana) genomes. A. thaliana centromeres comprise megabase satellite repeat arrays that load nucleosomes containing the CENH3 histone variant. Each chromosome contains a structurally polymorphic region of ~3–4 megabases, which lack crossovers and include the satellite arrays. This polymorphic region is flanked by ~1–2 megabase low-recombination zones. These recombination-suppressed regions are enriched for Gypsy/Ty3 retrotransposons, and additionally contain expressed genes with high genetic diversity that initiate meiotic recombination, yet do not crossover. We map crossovers at high-resolution in proximity to CEN3, which resolves punctate centromere-proximal hotspots that overlap gene islands embedded in heterochromatin. Centromeres are densely DNA methylated and the recombination landscape is remodelled in DNA methylation mutants. We observe that the centromeric low-recombining zones decrease and increase crossovers in CG (met1) and non-CG (cmt3) mutants, respectively, whereas the core non-recombining zones remain suppressed. Conclusion Our work relates the genetic and epigenetic organization of A. thaliana centromeres and flanking pericentromeric heterochromatin to the zones of crossover suppression that surround the CENH3-occupied satellite repeat arrays.